2009
DOI: 10.1007/s11605-008-0765-7
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Anastomotic Leakage After Pancreatic Head Resections by Dynamic Magnetic Resonance Imaging (dMRI)

Abstract: dMRI with SI(ratio) calculation provided reliable information for the prediction of pancreatic texture. Patients with a SI(ratio) >or= 1.1 had a 7.9-fold increased risk of anastomotic leakage and a prolonged hospital stay. SIC with measurements of SI(ratio) in dMRI could therefore define patients at risk for anastomotic leakage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 42 publications
1
32
0
1
Order By: Relevance
“…3,4,10,13 On the other hand, pancreatic fibrosis is thought to decrease the softness of the gland. [18][19][20][21][22]27 Recently, it has been shown that CT or magnetic resonance (MR) perfusion imaging can detect microcirculatory changes caused by collagen deposits in the liver and pancreas. [18][19][20]22,28,29 Romero-Gomez et al 28 studied liver fibrosis in patients with chronic hepatitis C and concluded that optical digital analysis of conventional CT images is effective in determining the stage and distribution of liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,4,10,13 On the other hand, pancreatic fibrosis is thought to decrease the softness of the gland. [18][19][20][21][22]27 Recently, it has been shown that CT or magnetic resonance (MR) perfusion imaging can detect microcirculatory changes caused by collagen deposits in the liver and pancreas. [18][19][20]22,28,29 Romero-Gomez et al 28 studied liver fibrosis in patients with chronic hepatitis C and concluded that optical digital analysis of conventional CT images is effective in determining the stage and distribution of liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22] In a recent study, we reported that patients with autoimmune pancreatitis show enhancement characteristics distinct from patients with adenocarcinoma on dualphase computed tomography (CT). 22 A delayed enhancement with a slow increase followed by a slow decline or a plateau was characteristic for a fibrotic pancreas in patients with autoimmune pancreatitis; a rapid increase followed by a rapid decrease indicated a "normal" pancreas with lower degrees of fibrosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most powerful and promising imaging modalities were ARFI elastography [35,36], which provides information about the elastic properties of the pancreas; contrast-enhanced CT, which reflects the enhancement characteristics of the pancreatic parenchyma; [37,38] MR images, which display the ratios of the signal intensity of the pancreas relative to hepatic, splenic, or muscular values on T1-weighted MRI [43,44], and time-signal intensity curves on dynamic contrast-enhanced MRI [18,46,47,49], in which the MR images reflect the histological degree of pancreatic fibrosis; and MDCT and/or MRI, which reflect the histological grade of pancreatic fatty infiltration [40,41,51]. US elastography, with either a transabdominal or an endoscopic approach, can be a useful, convenient, and inexpensive imaging tool in the diagnostic workup for various pancreatic pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the pancreatic TIC can be used to detect early fibrotic changes induced in the pancreatic remnant after PD that precede the functional deterioration of the pancreatic remnant [48]. Using the axial T1-weighted imaging sequences obtained from dynamic contrast-enhanced MRI of the pancreas before and at 25 and 60 s after the intravenous administration of contrast media, Dinter et al [49] calculated the muscle-normalized signal intensity curve of the pancreas with an SI ratio (SI ratio ) at the estimated transection line for the pancreas in 72 patients undergoing PD. The SI ratio = SI ea /SI pv : SI ea was defined as the SI of the pancreas in the early arterial phase, and SI pv as the portalvenous phase, after the application of contrast.…”
Section: Mri Studiesmentioning
confidence: 99%